Prevalence, risk and antibiogram of Listeria monocytogenes in raw chicken meat - Goh, Sur Guat (2013)
Chicken is a popular food in Malaysia. Consumption of poultry products has been increasing in the past decades. However, the contamination levels of Listeria monnocytogenes (L. monocytogenes) in retailed chicken meat remain uncertain. This research was conducted to study the prevalence and antibiotic resistance of L. monocytogenes in raw chicken meat and effects of clove extracts against L. monocytogenes isolates. This study also aimed to determine transmission of L. monocytogenes from raw to cooked chicken meat via cutting boards as well as the risk of acquiring listeriosis through consumption of raw chicken meat. A total of 210 samples were purchased from three hypermarkets and three wet markets in Selangor from September 2011 to January 2012. Most Probable Number (MPN) method had been used together with Polymerase Chain Reaction (PCR) and conventional plating for detection of L. monocytogenes in raw chicken meat. Prevalence of L. moncytogenes in raw chicken meat was found to be 20%, in which the prevalence of L. monocytogenes in samples purchased from hypermarkets (25.71%) was higher than those of wet markets (14.29%). L. monocytogenes was detected in chicken breasts, drumsticks and thigh at prevalences of 42.03%, 11.27% and 7.14% respectively. MPN-PCR showed higher sensitivity compared to MPN-plating. By using MPN-PCR, the prevalence of L. monocytogenes in chicken meat was 20%, while MPN-plating could only detect 9.52%. The density of L. monocytogenes found in the samples ranged from <3.0 to 16 MPNg-1. Twenty-three isolates of L. monocytogenes were recovered from raw chicken meat. All isolates showed resistance to at least one antibiotic tested. Eleven isolates (47.83%) were resistant to at least 8 antibiotics. The isolates showed highest resistance against chloramphenicol (69.57%) followed by tetracycline (60.87%). Resistance of L. monocytogenes isolates towards antibiotic demonstrates the importance of identifying novel antimicrobial agent to inactivate L. monocytogenes in food before consumption. Thus, clove extracts was used to inhibit the L. monocytogenes isolates. Clove extracts showed inhibitory effect on L. monocytogenes isolates. MIC (Minimal inhibitory concentration) and MBC (Minimal bactericidal concentration) of clove extracts ranged from 156.25 ± 0.00 to 1041.67 ± 360.84 and 520.83 ± 180.42 to 4166.67 ± 1443.38 μg/ml, respectively. A simulation study was conducted to determine the transmission of L. monocytogenes from raw to cooked chicken meat via polyethylene and wooden cutting boards. L. monocytogenes was found to contaminate cooked chicken meat regardless of the temperature of the chicken meat (room temperature or boiling temperature) and the material of the cutting boards when it is used within 30 min of contamination. Stepwise risk assessment was used to determine the risk of acquiring listeriosis by consumption of raw chicken meat. An estimate of worst case scenario showed that the risk of acquiring listeriosis for healthy population was 0.008 per 100,000 populations annually. The risk estimates were higher for AIDS patients (6.670 per 100,000), Diabetes Mellitus Type II patients (0.190 per 100,000) and elderly (0.060 per 100,000). Presence of L. monocytogenes in raw chicken meat is unavoidable, thus, consumers should be aware of the significance of L. monocytogenes to human health and the ways to prevent its contamination.